Spatiotemporal Distribution Characterization for Terahertz Waves Generated From Plasma Induced by Two-Color Pulses - Wang, Erli; Wang, Yulong; Sun, Wenfeng; Wang, Xinke; Feng, Shengfei; Han, Peng; Ye, Jiasheng; Zhang, Yan (Frontiers in Physics, 2021)
The spatiotemporal distribution of terahertz (THz) radiation from plasma has been demonstrated with the technology of THz focal-plane imaging. It has been found that the spatiotemporal distribution will vary with the frequency, as well as the length of plasma. A doughnut-shaped distribution appears in the lower frequency range, while the bell-shaped distribution corresponds to the higher frequency range. For plasmas with different lengths, their generated THz images in the time domain are similar, the THz images in the frequency domain as well. The spatiotemporal distributions are simulated with the off-axis-phase matching theory. All the findings will renew the understanding of the THz generation from plasma induced by two-color pulses.